PHYSICAL DEVELOPMENT DELAYS IN PRIMARY SCHOOL STUDENTS AND WAYS TO ELIMINATE THEM - Bekmanova Khurshida Shokirjonovna (Bright Mind Publishing, 2025)
This article provides a scientific analysis of cases of physical developmental delays in primary school students. The main causes of the problem are insufficient physical activity, improper nutrition, socio-economic environment, and environmental factors. Based on statistical data and scientific research, the consequences of delays behind are highlighted, and practical recommendations for eliminating these situations are given.
Keywords: Primary school, physical development, backwardness, healthy lifestyle, children's health, physical activity, nutrition, school health improvement.